2018
DOI: 10.1039/c7an02019h
|View full text |Cite
|
Sign up to set email alerts
|

Optimized polydopamine coating and DNA conjugation onto gold nanorods for single nanoparticle bioaffinity measurements

Abstract: Gold nanorods (NRs) have attracted a great deal of interest for a variety of biomedical and sensing applications. However, developing robust methods for biofunctionalizing NRs has continued to be challenging, especially for NR-DNA conjugates. This is due to the presence of cetyltrimethylammonium bromide (CTAB), which plays an essential role in controlling the anisotropic particle growth. In this article, we systematically explore the growth of a polydopamine (PDA) layer on a range of NR surfaces, comparing dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…In addition, the introduction of PDA also prolonged the blood circulation time of gold nanorods, where the half-life increased from 0.7 to 4.5 h. Cu­(II) was doped in the PDA layer, which endowed gold nanorods with MRI and chemotherapeutic functions. In a separate study, Azab et al explored the growth of PDA layer on positively or negatively charged gold nanorod surfaces . They studied the effect of different functional groups such as polyelectrolyte and alkanethiol deposited onto gold nanorod surfaces on the kinetics and thickness of the PDA layer.…”
Section: Surface Modificationmentioning
confidence: 99%
“…In addition, the introduction of PDA also prolonged the blood circulation time of gold nanorods, where the half-life increased from 0.7 to 4.5 h. Cu­(II) was doped in the PDA layer, which endowed gold nanorods with MRI and chemotherapeutic functions. In a separate study, Azab et al explored the growth of PDA layer on positively or negatively charged gold nanorod surfaces . They studied the effect of different functional groups such as polyelectrolyte and alkanethiol deposited onto gold nanorod surfaces on the kinetics and thickness of the PDA layer.…”
Section: Surface Modificationmentioning
confidence: 99%
“…Similarly, NaCl was then added to 0.15 m and allowed to react for another day. [112] DNA strands can also be attached to PDA coated probes and films using similar methods. [113][114][115] As described above, adding NaCl followed by incubation (salt aging) was performed to reach a high DNA density.…”
Section: Covalent Dna Attachmentmentioning
confidence: 99%
“…[99,107] Azab et al found a 45-50% decrease in surface density when the saltaging method was not used. [112] In addition to charge screening, an alkane, PEG, or polynucleotide spacer inserted between the amine/thiol functional group and the end of DNA could further increase the DNA packing density by reducing steric interactions and intermolecular repulsion of adjacent DNA strands at the surface of small NPs. [112,116] Figure 6.…”
Section: Covalent Dna Attachmentmentioning
confidence: 99%
See 2 more Smart Citations